PERANCANGAN DAN PENERAPAN SISTEM KANBAN DI PT XY - Dimas Herdiansyah (Jurnal Ilmiah Teknologi Infomasi Terapan, 2020)
PT XY is a company that often experiences minus production every month. The problem of late delivery of parts from the warehouse to the production line is due to the unstructured material supply system, resulting in a production hindrance that results in a late completion of the product. To meet the production target, additional overtime is carried out so that the costs borne by the company due to inaccurate material supply systems are high. This research tries to propose an information system in the form of kanban sending parts to the production line by using a kanban system which is expected to be able to anticipate the occurrence of line stops due to part shortages. This research succeeded in designing the kanban system, kanban cards and determining the number of kanban in circulation.